A New Approach for Accurate Identification of Allele State Based on Real-Time PCR for Biomedical Tasks - Benaguev, Ernest; Vladimirov, Ivan; Pavlova, Olga; Bogomaz, Denis (KnE Life Sciences, 2022)
Genotyping of single nucleotide polymorphisms (SNPs) is an important task in medicine, veterinary medicine and biology. Precise differentiation of SNPs can be challenging. Methods based onTaqman can lead to false positive results due to nonspecific annealing of the probe. The aim of this research was to develop a new approach for the accurate differentiation of SNPs based on real-time PCR with Taqmanprobes and their rivals.The rivals competed with the Taqmanprobes for annealing to the site. The rivals blocked the nonspecific allele so that the Taqmanprobe could not anneal to it. Thus,the Taqmanprobe only detected specific alleles.This approach madeit possible to fine-tune the diagnostic system by selecting the ratio of Taqmanprobes and rivals (in non-equimolar amounts too).The new approach was tested on several diagonally significant SNPs in veterinary medicine.Using Taqman probes and rival probes showed a significantly greater specificity and efficiency in the determination of both homozygotes and heterozygotes than when conventional systems based only on Taqmanwere used. Keywords: SNP, allele identification, real-time PCR, fluorescent dye